Oxidative Stress in Psoriasis Vulgaris Patients: Analysis of Asymmetric Dimethylarginine, Malondialdehyde, and Glutathione Levels - Gocer Gurok, Nese; Telo, Selda; Genc Ulucan, Busra; Ozturk, Savas (Mdpi, 2025)
Background and Objectives: Psoriasis vulgaris (PV) is a chronic inflammatory disease associated with oxidative stress. It has been reported that oxidative stress caused by disruption of redox signaling can cause molecular damage, activate dendritic cells, lymphocytes, and keratinocytes, and lead to angiogenesis, inflammation, cell necrosis, and apoptosis by increasing the levels of lipid peroxidation products. In this study, serum levels of asymmetric dimethylarginine (ADMA), malondialdehyde (MDA), and reduced glutathione (GSH) were analyzed to gain insight into the oxidative balance in patients with PV. Materials and Methods: This prospective study included 59 PV patients and 40 healthy volunteers as the healthy control group. Age, gender, body mass index (BMI), waist circumference, routine hematologic parameters [fasting blood glucose, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), blood lipid levels, hemogram parameters], disease duration, and disease severity were recorded on data forms. The levels of ADMA, MDA, and GSH were analyzed using the high-performance liquid chromatography (HPLC) method. Results: When analyzed in terms of demographic characteristics, no statistically significant difference was observed between the patient and control groups. When examined in terms of biochemical variables, white blood cell (WBC) values were found to be significantly higher in the patient group (t: 2.825; p < 0.05). Although waist circumference, BMI, glucose, CRP, ESR, lipids, platelet count, and systolic and diastolic blood pressure were higher in the patient group, this difference was not statistically significant (p > 0.05). ADMA (t: 4.532; p < 0.05) and MDA (t: 9.598; p < 0.05) values were found to be higher and GSH (t: -4.717; p < 0.05) values were found to be lower in the patient group compared to the control group. When correlation analysis was performed between the parameters, a significant relationship was found only between GSH values and ADMA values (r: -0.256; p < 0.05). Accordingly, as the patients' GSH values increased, ADMA values decreased. Conclusions: Increased WBC, ADMA, and MDA levels, and decreased GSH levels in PV patients reveal the critical role of oxidative stress and inflammation in the disease process. Evaluation of these biomarkers may contribute to the identification of new targets for the treatment of PV and the development of more effective management strategies.
Keywords: psoriasis; oxidative stress; ADMA; MDA; glutathione